Prediction of response to neoadjuvant chemoendocrine therapy in primary breast carcinomas - Makris, A; Powles, T J; Dowsett, M; Osborne, C K; Trott, P A; Fernando, I N; Ashley, S E; Ormerod, M G; Titley, J C; Gregory, R K; Allred, D C (Clinical cancer research, 1997)
Our aim was to determine whether biological molecular markers can predict response to neoadjuvant chemoendocrine therapy in patients with early breast cancer. Ninety patients (median age 56 years; range, 28-69 years) with primary operable breast carcinoma were studied. They were treated with four 3-weekly cycles of chemotherapy with mitozantrone, methotrexate (+/- mitomycin C), and tamoxifen prior to surgery. Fine-needle aspiration was used to obtain samples from patients prior to therapy, and the following parameters were assessed: estrogen receptor (ER), progesterone receptor (PgR), p53, Ki67, Bcl-2, and c-erbB-2 measured by immunocytochemistry, and ploidy and S-phase fraction (SPF) by flow cytometry. The tumors of 78% of the subjects responded (complete response, 9%; partial response, 69%) and 22% did not (no change, 20%; progressive disease, 2%). Response rates according to disease stage and patient age were as follows: T1, 74%; T2, 79%; T3/T4, 78%; age </=50 years, 76%; >50, 79% (P = not significant). Response rates for other parameters were as follows: ER-positive, 82%, and -negative, 70%; PgR-positive, 86%, and -negative, 71%; p53-positive, 74%, and -negative, 81%; Bcl-2-positive, 85%, and -negative 61%; c-erbB-2-positive, 57%, and -negative, 93%; Ki67 high, 77%, and low, 81%; SPF high, 77%, and low, 77%; aneuploid, 71%; and diploid, 85%. Only the difference for c-erbB-2 was statistically significant (P = 0.007). A trend for higher response rates to neoadjuvant chemoendocrine therapy for tumors that were positive for ER, PgR, and Bcl-2 was observed but did not reach statistical significance. Tumors negative for c-erbB-2 had a higher response rate, which was statistically significant. In contrast, Ki67, ploidy, SPF, and p53 failed to predict for response.